Separate and Unequal: The Kerner Commission and the Unraveling of American Liberalism - Steven M. Gillon (Basic Books, 2018)
In Separate and Unequal, New York Times bestselling historian Steven M. Gillon offers a revelatory new history of the National Advisory Commission on Civil Disorders -- popularly known as the Kerner Commission. Convened by President Lyndon Johnson after riots in Newark and Detroit left dozens dead and thousands injured, the commission issued a report in 1968 that attributed the unrest to "white racism" and called for aggressive new programs to end discrimination and poverty. "Our nation is moving toward two societies," it warned, "one black, and one white -- separate and unequal."